1993
DOI: 10.1111/j.1525-1446.1993.tb00062.x
|View full text |Cite
|
Sign up to set email alerts
|

AIDS‐Related Knowledge, Fear, and Behavioral Change Among Nurses in Taiwan

Abstract: Current literature documents a phenomenon of fear that affects the willingness of health care professionals to care for persons with acquired immunodeficiency syndrome (AIDS). We attempted to identify differences between nurses who exhibit fearful attitudes toward AIDS and those who do not, based on knowledge and behavior. Taiwan, site of the study, is only beginning to identify the first of its citizens with AIDS. The subjects were a population of caregivers from a culture with little exposure, therefore, eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
1
9
1
Order By: Relevance
“…Firstly, the study was from only one hospital and, therefore, the results might not reflect nurses’ attitudes and concerns in other hospitals in Taiwan. However, our results are comparable to results from other Taiwanese studies where more than one hospital was sampled 3,4 , 15 . Secondly, bias of non‐responders is always a major concern in cross‐sectional studies.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Firstly, the study was from only one hospital and, therefore, the results might not reflect nurses’ attitudes and concerns in other hospitals in Taiwan. However, our results are comparable to results from other Taiwanese studies where more than one hospital was sampled 3,4 , 15 . Secondly, bias of non‐responders is always a major concern in cross‐sectional studies.…”
Section: Discussionsupporting
confidence: 88%
“…Nearly 20% also thought that freezing destroys HIV. Other studies from Taiwan have also shown a general lack of AIDS/HIV knowledge 4,15 . Yeh et al.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This is evident in a study of nursing and medical students in Manila by Tan (1992), where 96% of the respondents blamed at least one ‘high‐risk’ group, especially women sex workers, for the spread of HIV in the Philippines. A study of nurses in Taiwan reports that 87% of respondents, if hospitalized, would not share a room with a person with HIV/AIDS ( Wang et al . 1993 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…3,4 As instigator and corresponding author of the study of Juan et al, I wish to correct the conclusions of Okpala et al in case their statements are cited incorrectly in the future.…”
Section: Nurses' Knowledge Of Hiv/aidsmentioning
confidence: 99%